Current management strategies of emphysematous pyelonephritis – Our institutional experience - Rajkumar Ramakrishnan; Senthilkumar Poovathai; Rajasekar Sundaram; Shravankumar Savadatti; Gopu Rakesh Vamsi; Sammohit Gulakavarapu (Asian Journal of Medical Sciences, 2023)
Background: Emphysematous pyelonephritis (EPN) is commonly seen in uncontrolled diabetes patients. Appropriate identifications of risk factors and timely management underline the outcome in such patients. Aims and Objectives: The objectives of this study were to study the various risk factors, clinical features, and radiological classification of EPN. The specific objective of this study was to study various management approaches such as medical management, minimally invasive procedures, and nephrectomy. Materials and Methods: We prospectively analyzed 128 patients from January 2021 to July 2022 – documented clinical data, laboratory data, imaging findings, interventions, and outcomes of patients with EPN. Results: Among 128 patients, 96 were female and 32 were male. Among them, 110 were diabetic. All had symptoms of fever and flank pain. Based on CT findings, EPN was classified as Class 1 (n=30), Class 2 (n=54), Class 3a (n=24), Class 3b (n=16), and Class 4 (n=4). Escherichia coli (n=75) most common organism grown. Majority were treated with antibiotics. Thirty-six patients underwent percutaneous drainage, 12 patients percutaneous nephrostomy, and 25 patients subjected to DJ stenting. Nephrectomy was done in 7.8%. Mortality rate in our study was 6.25%. Conclusion: EPN management requires multidisciplinary approach including adequate hydration and electrolyte imbalance management, broad spectrum antibiotics, strict glycemic control, effective urinary drainage, and lastly nephrectomy.